FEE AUDIT MEMODERASI PENGARUH KUALITAS AUDIT TERHADAP MANAJEMEN LABA DAN BIAYA MODAL EKUITAS - Ari Puryanti Dewi, Ni Putu; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 20 No 3 (2017), 2017)
This study aims to provide empirical evidence about the audit fee moderating effect the quality of audit on earnings management and the cost of equity capital. The object of this research is manufacturing companies listed in Indonesia Stock Exchange 2013-2015 period. The sampling method using purposive sampling method and obtained 46 samples of the company. Data collection method used was non-participant observation method to download data from the official website of the Stock Exchange. Testing the hypothesis in this study using linear regression analysis. Hypothesis testing results show that the variable quality of audit negative effect on earnings management and the cost of equity capital, while the variable audit fee strengthen or as pure moderator effect the quality of audit  on earnings management and the cost of equity capital.
Keywords: Audit Fee, Quality of Audit, Earnings Management, The Cost of Equity Capital